2013
DOI: 10.1021/ol403186k
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of Atmospheric CO2 as Carbonate Inside the Molecular Cavity of a New Tripodal Hexaurea Receptor

Abstract: A new hexaurea receptor has been synthesized, which absorbs atmospheric CO2 to produce an air-stable solid carbonate complex under normal conditions. Structural analysis of the carbonate complex with this receptor suggests that the carbonate is fully encapsulated within its highly organized intramolecular cavity via twelve strong NH···O bonds in the range of 2.703(3) – 2.989(3) Å from six urea units, with each anionic oxygen coordinated via four NH···O bonds with two urea groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…42 The crystal structure of the sulfate complex showed that all six ureas were arranged optimally along each edge of the tetrahedral anion, forming totally 12 hydrogen bonds (N-O distances ranging from 2.903 to 3.157 Å, average 2.992 Å; N-HÁ Á ÁO angles from 1431 to 1731, average 1611) (Fig. 43 Wu and coworkers further studied three ferrocenyl-functionalized tripodal hexakis-urea anion receptors with ortho-(32a), meta-(32b), and para-phenylene (32c) linkers, which showed strong binding affinities toward sulfate ions. The excellent complementarity as well as the high chelate effect enable the host to efficiently extract sulfate ions from aqueous NaNO 3 -Na 2 SO 4 solution into CDCl 3 as revealed by 1 H NMR.…”
Section: àmentioning
confidence: 99%
“…42 The crystal structure of the sulfate complex showed that all six ureas were arranged optimally along each edge of the tetrahedral anion, forming totally 12 hydrogen bonds (N-O distances ranging from 2.903 to 3.157 Å, average 2.992 Å; N-HÁ Á ÁO angles from 1431 to 1731, average 1611) (Fig. 43 Wu and coworkers further studied three ferrocenyl-functionalized tripodal hexakis-urea anion receptors with ortho-(32a), meta-(32b), and para-phenylene (32c) linkers, which showed strong binding affinities toward sulfate ions. The excellent complementarity as well as the high chelate effect enable the host to efficiently extract sulfate ions from aqueous NaNO 3 -Na 2 SO 4 solution into CDCl 3 as revealed by 1 H NMR.…”
Section: àmentioning
confidence: 99%
“…This orientation of the two rings is in agreement with its p -nitrophenyl-substituted analogue with the sulfate complex, 52 but in contrast to its pentafluoro-substituted analogue 2 with the carbonate complex in which the corresponding two rings are parallel with respect to each other. 54 To the best of our knowledge, a perfect C 3 -symmetric sulfate complex with a synthetic receptor has not been reported previously.…”
Section: Results and Discussionmentioning
confidence: 93%
“…In an effort to synthesize C 3 -symmetric urea-based receptors with a higher order of binding sites, we recently synthesized a pentafluoro-substituted hexaurea receptor 2 that was found to encapsulate one carbonate anion; however, we were unsuccessful in obtaining the crystals of the sulfate complex with this receptor. 54 To examine the influence of attached groups on the binding strength and selectivity, we have been further interested in functionalizing the core cavity and synthesized the m -nitrophenyl-substituted hexaurea receptor 1 . Herein, we report that the receptor 1 assembles the urea groups at accurate positions around a tetrahedral sulfate anion, thus forming an ideal C 3 -symmetric sulfate complex from the interactions of all NH-binding sites with the anion and NH···π interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some specially designed organic compounds have shown great potential for DAC. For example, in 2014, Hossain group developed an organic compound with six urea groups which absorbed atmospheric CO 2 as CO 3 2− via 12 strong N—H∙∙∙O bonds under mild conditions ( Pramanik et al., 2014 ). In 2017, Custelcean et al.…”
Section: Introductionmentioning
confidence: 99%